2019
DOI: 10.1158/1078-0432.ccr-19-0405
|View full text |Cite
|
Sign up to set email alerts
|

Localized Treatment with Oncolytic Adenovirus Delta-24-RGDOX Induces Systemic Immunity against Disseminated Subcutaneous and Intracranial Melanomas

Abstract: Purpose: Intratumoral injection of oncolytic adenovirus Delta-24-RGDOX induces efficacious antiglioma immunity in syngeneic glioma mouse models. We hypothesized that localized treatment with the virus is effective against disseminated melanomas.Experimental Design: We tested the therapeutic effect of injecting Delta-24-RGDOX into primary subcutaneous (s.c.) B16-Red-FLuc tumors in s.c./s.c. and s.c./intracranial (i.c.) melanoma models in C57BL/6 mice. Tumor growth and in vivo luciferase-expressing ovalbumin-spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 51 publications
5
31
0
Order By: Relevance
“…In addition to this primary effect, oncolytic viruses are also able to stimulate the immune system against cancer cells, in which the immune system is silenced by the TME 320 . The use of improved oncolytic adenovirus treatment regimens has demonstrated therapeutic activity in immunocompetent C57BL/6 mouse models by stimulating an influx of CD8 + T cells specific to tumor-associated antigens 321 , 322 . Moreover, in human patients, viral treatments have been shown to induce a tumor macrophage phenotypic shift 323 .…”
Section: Viral Therapymentioning
confidence: 99%
“…In addition to this primary effect, oncolytic viruses are also able to stimulate the immune system against cancer cells, in which the immune system is silenced by the TME 320 . The use of improved oncolytic adenovirus treatment regimens has demonstrated therapeutic activity in immunocompetent C57BL/6 mouse models by stimulating an influx of CD8 + T cells specific to tumor-associated antigens 321 , 322 . Moreover, in human patients, viral treatments have been shown to induce a tumor macrophage phenotypic shift 323 .…”
Section: Viral Therapymentioning
confidence: 99%
“…OX40 is not constitutively expressed on resting naïve T-cells and plays a key role in the survival and homeostasis of effector and memory T-cells, and it regulates the differentiation and function of Foxp3+ Tregs [ 59 ]. H. Jiang et al have recently showed that OX40L-armed Onc.Ad (Delta-24-RGDOX) has a stronger anticancer efficacy compared to its predecessor Delta-24-RGD, triggering a greater tumor-specific lymphocyte activation and a proliferation of TAAs-specific CD8 + T-cells in two mouse glioma models [ 60 ]. In the same model, a synergistic therapeutic effect was observed by the intra-tumoral injection of Delta-24-RGDOX and an anti-PD-L1 antibody [ 61 ].…”
Section: Exploring the Tumor Microenvironment And Its Modulation Bmentioning
confidence: 99%
“…DNX-2440 (Delta-24-RGDOX) is an immunomodulatory recombinant selectively replication-competent serotype 5 strain Ad-encoding OX40 ligand (OX40L) driven by the cytomegalovirus (CMV) promoter. The protein is able to activate T cells via interaction with its receptor on the surface of T lymphocytes [ 28 , 29 ].…”
Section: Molecular Strategies For Viral Gene Therapy Of the Gbmmentioning
confidence: 99%